1995
DOI: 10.1002/ajmg.1320570230
|View full text |Cite
|
Sign up to set email alerts
|

Batten disease and the ATP synthase subunit c turnover pathway: Raising antibodies to subunit c

Abstract: Analysis of storage bodies in the ceroid-lipofuscinoses (Batten disease) has demonstrated a high protein content suggestive of a proteinosis. Direct N-terminal sequencing has shown that subunit c of mitochondrial ATP synthase is specifically stored in the disease in sheep and cattle, and in the human late infantile and juvenile diseases, as well as in 3 breeds of dogs. No differences have been found between the stored subunit c and that in normal mitochondria. No other mitochondrial components are stored. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Use of antiserum raised against full-length SCMAS [22] yielded similar results (not shown) as the antibody against the amino terminus. It is therefore likely that the edges of arrays were stained preferentially because they provided better accessibility to the antibody.…”
Section: Observation Of Scmas At the Electron Microscopic Levelmentioning
confidence: 53%
“…Use of antiserum raised against full-length SCMAS [22] yielded similar results (not shown) as the antibody against the amino terminus. It is therefore likely that the edges of arrays were stained preferentially because they provided better accessibility to the antibody.…”
Section: Observation Of Scmas At the Electron Microscopic Levelmentioning
confidence: 53%
“…Btn1p is 39% identical and 59% similar to human Cln3 protein, mutations in which result in the lysosomal storage disorder Batten disease (11,22). Batten disease is characterized by accumulation of lipopigments in the lysosome (6,8,14,20,21). In summary, btn1⌬ cells are known to have an altered regulation of vacuolar pH and a decrease in the ability to transport basic amino acids into the vacuole, features which presumably account for the decreased levels of basic amino acids in the vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that yeast strains lacking Btn1p were resistant to D-(Ϫ)-threo-2-amino-1-[p-nitrophenyl]-1,3-propanediol (ANP) and that this phenotype was complemented by expression of the human Cln3 protein, indicating that yeast Btn1p and the human Cln3 protein have some functional overlap (17). Furthermore, the degree of ANP resistance was correlated with point mutations identified in the human CLN3 gene that are associated with less-severe forms of Batten disease, further establishing the functional equivalence of Btn1p and the human Cln3 protein (15). The human Cln3 protein, like Btn1p, has been localized to the lysosome, denoted the vacuole in yeast (3,7,9,10,18).…”
mentioning
confidence: 90%
“…A characteristic of Batten disease is the lysosomal storage or accumulation of lipopigments such as lipofuscin in all cell types. A predominant component of this storage material is proteolipid subunit c of mitochondrial ATP synthase (6,12,14,15). However, despite knowledge of the genetic defect and evidence for Batten disease being a lysosomal storage disease, an understanding of the molecular basis for Batten disease remains elusive.…”
mentioning
confidence: 99%